MAIN CHARACTERISTICS OF MODERN LANGUAGE TEACHING METHODS - Kubaeva Nafisa; Ulmasova Dinara; Djanzakova Matluba (Innovate Conferences, 2025)
The article examines the key differences between traditional and modern methods of teaching English, as well as their impact on language acquisition. Traditional methods, such as the grammar-translation method and the audio-linguistic approach, emphasize grammar accuracy, vocabulary memorization, and repetitive exercises. At the same time, modern techniques, including communicative learning (CLT) and task-based learning (TBL), focus on developing fluency, communication, and the practical application of language skills.
Keywords: teaching methods, traditional methods, modern methods, communicative approach, language competence, technologies in teaching.